Quantification of the interaction forces between metals and graphene by quantum chemical calculations and dynamic force measurements under ambient conditions - Lazar, Petr; Zhang, Shuai; Safářová, Klára; Li, Qiang; Froning, Jens Peter; Granatier, Jaroslav; Hobza, Pavel; Zbořil, Radek; Besenbacher, Flemming; Dong, Mingdong; Otyepka, Michal (ACS nano, 2013)
The two-dimensional material graphene has numerous potential applications in nano(opto)electronics, which inevitably involve metal graphene interfaces.Theoretical approaches have been employed to examine metal graphene interfaces, but experimental evidence is currently lacking. Here, we combine atomic force microscopy (AFM) based dynamic force measurements and density functional theory calculations to quantify the interaction between metal-coated AFM tips and graphene under ambient conditions. The results show that copper has the strongest affinity to graphene among the studied metals (Cu, Ag, Au, Pt, Si), which has important implications for the construction of a new generation of electronic devices. Observed differences in the nature of the metal-graphene bonding are well reproduced by the calculations, which included nonlocal Hartree-Fock exchange and van der Waals effects.
Keywords: Graphite; mikroskopie atomárních sil; grafit; Metals; Quantum Theory; kvantová teorie; kovy; Microscopy, Atomic Force